English Teachers' Efforts Towards Language Acquisition of Students With Mental Retardation - Nashruddin, Nashruddin; Aisyah, Sitti; Latief, Syekh Adiwijaya; Ilmi, Musyakirah Nur (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to describe how students with mental retardation acquire language, and to find out the efforts of English teachers through multicultural-based education in supporting the language acquisition of students with mental retardation. Using a descriptive qualitative method, this study involved 10 students with mental retardation and one English teacher at a special school (SLB) in Maros Regency. Data was collected through observation and interviews to explore learning practices and teacher interactions with students. The data analysis technique is thematic analysis, which allows researchers to identify the main patterns and themes from the data obtained. Research findings indicate five stages of language acquisition by students with mental retardation: preproduction, early production, speech emergency, intermediate fluency, and advanced fluency. In addition, it was found that English teachers make five main efforts in multicultural learning: content integration, knowledge construction, equity pedagogy, prejudice reduction, and empowering school with culture and social structure. This research provides a new perspective by emphasizing the importance of integrating multicultural values ​​into language teaching strategies that are adaptive to students' special needs. The implications of this research suggest that inclusive and multicultural language education has the potential to improve the language skills of children with special needs and create a more equitable and empowering learning environment.